IMPLEMENTASI STRATEGI PEMBELAJARAN AKHLAK GURU PENDIDIKAN AGAMA ISLAM DI MTSN 1 PURWAKARTA - Abduh Dzul Fahmie; Lian Primadita; Enan Kusnandar (PANDU : Jurnal Pendidikan Anak dan Pendidikan Umum, 2026)
This study examines effective moral (akhlak) learning strategies implemented at through a comparative analysis based on teacher interviews. The scope of this article focuses on identifying instructional strategies applied in Akidah Akhlak classes, analyzing their effectiveness, and comparing teachers’ perspectives regarding student engagement and character development outcomes. The study falls within the field of Islamic education and moral pedagogy, particularly strategy-based instructional analysis at the junior secondary level. A qualitative descriptive method was employed, using semi-structured interviews with selected teachers as the primary data source. Data were analyzed through data reduction, categorization, comparison, and conclusion drawing. The findings reveal that active learning strategies, contextual approaches, modeling (uswah hasanah), and reflective discussions are considered the most effective methods in fostering students’ moral awareness and behavior. Differences among teachers mainly relate to implementation techniques rather than core objectives. The study concludes that collaborative, student-centered strategies supported by teacher role-modeling significantly enhance moral internalization and classroom engagement in Islamic moral education.